2018
DOI: 10.3390/ma11112308
|View full text |Cite
|
Sign up to set email alerts
|

A Facile and Low-Cost Method to Produce Ultrapure 99.99999% Gallium

Abstract: As one of the critical raw materials, very pure gallium is important for the semiconductor and photoelectric industry. Unfortunately, refining gallium to obtain a purity that exceeds 99.99999% is very difficult. In this paper, a new, facile and efficient continuous partial recrystallization method to prepare gallium of high purity is investigated. Impurity concentrations, segregation coefficients, and the purification effect were measured. The results indicated that the contaminating elements accumulated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…Owing to the difference in the atomic radius and electronegativity between Ga and impurity elements, the impurity atoms attached to the growth tip entered into the Ga lattice or lattice gap, causing the growth defect of Ga crystal [18,19,20]. This indicated that the removal of impurity elements decreased with the progress of crystallization and was consistent with the literature data [16].…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Owing to the difference in the atomic radius and electronegativity between Ga and impurity elements, the impurity atoms attached to the growth tip entered into the Ga lattice or lattice gap, causing the growth defect of Ga crystal [18,19,20]. This indicated that the removal of impurity elements decreased with the progress of crystallization and was consistent with the literature data [16].…”
Section: Resultssupporting
confidence: 82%
“…In a previous study, the effect of cooling water flow on the crystallization process was primarily investigated [16]. The results revealed that when the cooling water flow rate was 30 L·h −1 , the growth rate of gallium crystal near the outlet of the crystallizer was slightly lower than that in other regions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations